Social needs screening and referral in pediatric primary care clinics: a multiple case study - Rachel E. Massar; Carolyn A. Berry; Margaret M. Paul (BMC, 2022)
Abstract Background Unmet social risks such as housing, food insecurity and safety concerns are associated with adverse health outcomes in adults and children. Experimentation with social needs screening in primary care is currently underway throughout the United States. Pediatric primary care practices are well-positioned to amplify the effects of social needs screening and referral programs because all members of the household have the potential to benefit from connection to needed social services; however, more research is needed to determine effective implementation strategies. Methods To describe common implementation barriers and facilitators, we conducted 48 in-depth qualitative interviews with leadership, providers and staff between November 2018 and June 2019 as part of a multiple case study of social needs screening and referral programs based out of four pediatric ambulatory care clinics in New York City. Interviews were recorded, transcribed and coded using a protocol-driven, template-based rapid analysis approach designed for pragmatic health services research. In addition to analyzing content for our study, we delivered timely findings to each site individually in order to facilitate quality improvement changes in close-to-real time. Results Effective implementation strategies included tailoring screening tools to meet the needs of families seen at the clinic and reflect the resources available in the community, hiring dedicated staff to manage the program, building strong and lasting partnerships with community-based organizations, establishing shared communication methods between partners, and utilizing technology for efficient tracking of screening data. Respondents were enthusiastic about the value of their programs and the impact on families, but remained concerned about long-term sustainability after the grant period. Conclusion Implementation of social needs screening and referral interventions is dependent on contextual factors including the nature of family needs and the availability of intraorganizational and community resources to address those needs. Additional research is needed to prospectively test promising implementation strategies that were found to be effective across sites in this study. Sustainability of programs is challenging, and future research should also explore measurable outcomes and payment structures to support such interventions in pediatric settings, as well as aim to better understand caregiver perspectives to improve engagement.